2015
DOI: 10.1016/j.bbr.2015.02.048
|View full text |Cite|
|
Sign up to set email alerts
|

Docosahexaenoic acid partially ameliorates deficits in social behavior and ultrasonic vocalizations caused by prenatal ethanol exposure

Abstract: Prenatal ethanol exposure disrupts social behavior in humans and rodents. One system particularly important for social behavior is the somatosensory system. Prenatal ethanol exposure alters the structure and function of this area. Docosahexaenoic acid (DHA), an omega 3 polyunsaturated fatty acid, is necessary for normal brain development and brains from ethanol-exposed animals are DHA deficient. Thus, we determined whether postnatal DHA supplementation ameliorated behavioral deficits induced by prenatal ethano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 108 publications
(121 reference statements)
4
43
0
1
Order By: Relevance
“…While a three-trimester high-dose exposure has been shown to increase USV, a moderate dose over the same timespan did not (Marino, Cronise, Lugo, & Kelly, 2002; Ness & Franchina, 1990). Interestingly, a moderate first- and second-trimester exposure actually decreased USV (Wellmann, George, Brnouti, & Mooney, 2015). USV changes appear to be dependent upon dose as well as timing of exposure.…”
Section: Effects On Social Behaviormentioning
confidence: 95%
See 3 more Smart Citations
“…While a three-trimester high-dose exposure has been shown to increase USV, a moderate dose over the same timespan did not (Marino, Cronise, Lugo, & Kelly, 2002; Ness & Franchina, 1990). Interestingly, a moderate first- and second-trimester exposure actually decreased USV (Wellmann, George, Brnouti, & Mooney, 2015). USV changes appear to be dependent upon dose as well as timing of exposure.…”
Section: Effects On Social Behaviormentioning
confidence: 95%
“…3). The majority of rodent studies show that aggressive play is decreased in adolescent and adult males across PAE exposures (Charles Lawrence, Cale Bonner, Newson, & Kelly, 2008; Kelly & Dillingham, 1994; Lugo, Marino, Cronise, & Kelly, 2003; Meyer & Riley, 1986; Wellmann et al, 2015). However, some studies have shown increases in wrestling behaviors in males (Hamilton et al, 2010, 2014; Royalty, 1990).…”
Section: Effects On Social Behaviormentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, alcohol may become appealing to these individuals due to its ability to facilitate interactions with peers [2022]. Social behavior of laboratory rodents is sensitive to prenatal ethanol exposure as well, with alterations in adolescent-characteristic [2327] and adult-typical forms of social interactions [23, 2830] evident following chronic fetal exposure to ethanol. Furthermore, our previous research has shown that in Long Evans rats prenatal exposure to a single, binge-like dose of ethanol on gestational day (G)12 (early neural generation), but not on G7 (gastrulation) or G15 (mid-neuronal generation), reproducibly results in sex- and age of testing-dependent social deficits.…”
Section: Introductionmentioning
confidence: 99%